Ekplorasi Etnomatematika Kain Tenun Kampung Bokuna di Kecamatan Wewewa - Dona, Yunita; Lede, Yulius Keremata; Making, Samuel Rex Mulyadi; Lubur, Dorothea Novia Ludo (Indo-MathEdu Intellectuals Journal, 2024)
In general, the North Wewewa Wewewa Woven Fabric of Bokuna Village is passed down from the ancestors and followed until now this Woven Fabric has beautiful motifs made based on daily life and also from nature. Ethnomathematics is a bridge between culture and mathematics, ethmomathematics is adapted by cultural groups to see that the culture contains mathematical aspects. This research aims to find out the concept of geometry in Woven Fabrics. The data collected is in the form of documentation, interviews, and observation results. The type of research used in qualitative descriptive is to describe the mathematical elements contained in woven fabrics. Data collection uses observation and interviews. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the analysis show that Woven Fabrics are sacred crafts that are inherited from ancestors or from generation to generation. In the study, the researcher found several one-dimensional and two-dimensional buildings. The geometric shapes found by the researcher are: rectangular shape on the entire shape of the woven fabric, an equilateral triangle shape on the mamuli motif, an isosceles triangle shape on the flower motif, a bele ketupat shape on the star motif, a rectangular shape on the entire woven fabric, a square shape on the butterfly motif